Перспективы обновления содержания образования в практико-ориентированных дисциплинах специальности «профессиональное обучение» - Жигитов, А.Б.; Комиссаров, С.В. (My University, 2016)
The production is characterized by the rapid pace of technological development. The aim of article is analysis of the current state "Technology" of the educational and the implementation of robotics in school, by the introduction of elective courses in this area. Recommendations for updating the content of education in the practice-oriented disciplines.
Keywords: robotics; technology; practice-oriented disciplines